2019
DOI: 10.3389/fsurg.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

De novo OAB After ATOMS: An Underestimated Problem or a Rare Side Effect?

Abstract: Background: The urinary incontinence system ATOMS (A.M.I., Austria) generates suburethral compression through its sphincter cushion. To what extent the ATOMS may lead to overactive bladder (OAB) symptoms or which risk factors for these symptoms exist remain unknown to date. We report on our multicentre evaluation on the prevalence, status, and therapy of OAB after ATOMS. Methods: Between 10/09 and 01/17, a total of 361 patients received an ATOMS device in Vienna and Halle. A prerequisite for surgery was persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
3
2
Order By: Relevance
“…On the other hand, de novo urge incontinence is typically a late complication, but an infrequent one (1.9%). This finding has been recently reported, 21 but studies with urodynamic data looking for obstruction and detrusor overactivity should better clarify the cause and significance of de novo OAB after ATOMS placement. One cannot ignore that the appearance of de novo OAB might simply represent the aging of the cohort.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, de novo urge incontinence is typically a late complication, but an infrequent one (1.9%). This finding has been recently reported, 21 but studies with urodynamic data looking for obstruction and detrusor overactivity should better clarify the cause and significance of de novo OAB after ATOMS placement. One cannot ignore that the appearance of de novo OAB might simply represent the aging of the cohort.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies with ATOMS have reported that irradiation is a risk factor for complications 28 and also for the development of de novo OAB symptoms 29 . However, the present study runs contrary to these observations, probably because the methodology we used allows a better comparison.…”
Section: Discussioncontrasting
confidence: 82%
“…27 Previous studies with ATOMS have reported that irradiation is a risk factor for complications 28 and also for the development of de novo OAB symptoms. 29 However, the present study runs contrary to these observations, probably because the methodology we used allows a better comparison. In observational studies in which randomization is not possible, propensity score methods are used to reduce the bias in estimating treatment effects.…”
Section: Discussioncontrasting
confidence: 77%
“…The fact, that preoperative maximum cystometric volume in both cases were lower than volume at 1 st DO in postoperative surgery let us assume, that preoperative DO could be underestimated due to early urine leakage. Schoenburg et al (14) found no de novo DO in their prospective study in 361 patients with an ATOMS. Open to debate is the fact that urodynamic testing was not done regularly in the preoperative phase and that the postoperative symptoms of an overactive bladder were initially recorded only via questionnaires.…”
Section: Queissert Et Al Urodynamic Analysis Of Atomsmentioning
confidence: 90%